AFFILIATION NEEDS, LONELINESS, AND FEAR OF MISSING OUT (FOMO) IN ADOLESCENTS - Andini, Kartika Dwi; Effy Wardati Maryam (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study explores the relationship between the need for affiliation, loneliness, and Fear of Missing Out (FOMO) among adolescents, a group particularly vulnerable to social anxiety due to their intensive use of social media. Method: Utilizing a quantitative approach, the research involved 349 adolescents selected through accidental sampling from a population of 1,996,825 in Sidoarjo. Data were analyzed using multiple linear regression with the JASP version 17 software to assess the predictive roles of the need for affiliation and loneliness on FOMO. Results: The findings revealed a significant relationship between both the need for affiliation and loneliness with FOMO, with a p-value of 0.001, indicating that adolescents experiencing stronger desires for social connection and higher levels of loneliness are more likely to exhibit FOMO. Novelty: This study contributes to the limited body of research on FOMO in Indonesian adolescents by integrating psychosocial variables such as affiliation needs and loneliness, emphasizing the critical need for early interventions to manage digital-era social anxieties and promote healthier online engagement.